The Regional Sports Academy : Suriname plots region's sports course (2012)
Looks at the origin and expected impact of the Regional Sports Academy (RSA) , a regional project initiated by the Government of Suriname, and launched in that country on 8 March 2012.
Keywords: SPORTS